2020
DOI: 10.1029/2019gl086172
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Recrystallization Can Produce Porosity in Shear Zones

Abstract: Creep cavities are increasingly recognized as an important syn-kinematic feature of shear zones, but much about this porosity needs investigation. Largely, observations of creep cavities are restricted to very fine grained mature ultramylonites, and it is unclear when they developed during deformation. Specifically, a question that needs testing is should grain size reduction during deformation produce creep cavities? To this end, we have reanalyzed the microstructure of a large shear strain laboratory experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Journal of Geophysical Research: Solid Earth cavities (Fusseis et al, 2009;Gilgannon et al, 2020;Menegon et al, 2015), grain boundaries (Kruhl et al, 2013;Mancktelow et al, 1998), or well-developed cleavage (Babuska & Cara, 1991;Kern & Wenk, 1990;. With the FEM approach shown here, future studies could focus on characterizing the effect of real fracture networks, mineral phase, CPO, and microstructural arrangement data mapped from EBSD on the elastic anisotropic of shear zone rocks (Zhong et al, 2014).…”
Section: 1029/2019jb019029mentioning
confidence: 99%
See 1 more Smart Citation
“…Journal of Geophysical Research: Solid Earth cavities (Fusseis et al, 2009;Gilgannon et al, 2020;Menegon et al, 2015), grain boundaries (Kruhl et al, 2013;Mancktelow et al, 1998), or well-developed cleavage (Babuska & Cara, 1991;Kern & Wenk, 1990;. With the FEM approach shown here, future studies could focus on characterizing the effect of real fracture networks, mineral phase, CPO, and microstructural arrangement data mapped from EBSD on the elastic anisotropic of shear zone rocks (Zhong et al, 2014).…”
Section: 1029/2019jb019029mentioning
confidence: 99%
“…Kern et al (2008) suggest that low aspect ratio intercrystalline and intracrystalline microfractures related to biotite minerals should close at high effective pressures (>100 MPa), but Kern and Wenk (1990) conclude that aligned microfractures with foliation in mylonites remain open for effective pressures <50 MPa. Moreover, porosity in shear zone rocks can be as high as 8% (Géraud et al, 1995), and in addition to microfractures, porosity can be present in creep Journal of Geophysical Research: Solid Earth cavities (Fusseis et al, 2009;Gilgannon et al, 2020;Menegon et al, 2015), grain boundaries (Kruhl et al, 2013;Mancktelow et al, 1998), or well-developed cleavage (Babuska & Cara, 1991;Kern & Wenk, 1990;. With the FEM approach shown here, future studies could focus on characterizing the effect of real fracture networks, mineral phase, CPO, and microstructural arrangement data mapped from EBSD on the elastic anisotropic of shear zone rocks (Zhong et al, 2014).…”
Section: The Effect Of Open Grain Boundaries and Microfractures On P-wave Speedsmentioning
confidence: 99%
“…Mechanical phase mixing can occur by dynamic recrystallization coupled with grain switching during grain boundary sliding (Farla et al, 2013; Linckens et al, 2014), the sequential formation, attenuation (stretching), and disaggregation of compositional layering (Cross & Skemer, 2017) and/or the nucleation of well‐mixed grains at interphase triple junctions (Bercovici & Skemer, 2017). Chemical phase mixing, on the other hand, may involve the formation of a well‐mixed metamorphic reaction product (Dijkstra et al, 2002; Kenkmann & Dresen, 2002; Kruse & Stünitz, 1999; Marti et al, 2018; Newman et al, 1999), the exchange of chemical species between phases (Tasaka et al, 2017), and/or the precipitation of phases into dilational sites (Kenkmann & Dresen, 2002; Kilian et al, 2011; Platt, 2015) including creep cavities formed via grain boundary sliding (Czertowicz et al, 2016; Lopez‐Sanchez & Llana‐Fúnez, 2018; Menegon et al, 2015; Précigout et al, 2017; Viegas et al, 2016), Zener‐Stroh cracking (Gilgannon et al, 2017), or dynamic recrystallization (Gilgannon et al, 2020). Chemical phase mixing mechanisms may be extremely efficient, since well‐mixed reaction products can form even in the absence of deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Gilgannon et al 14 recently used a statistical approach to highlight micro-cavities emerging during dynamic recrystallization of experimentally deformed Carrara marble. They proposed that micro-pores may arise from sub-grain rotation with many implications, but without expanding much on the mechanism itself.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates previous observations that documented the presence of micro-pores in polymineralic shear zones dominated by dislocation creep 5 . Moreover, statistical characterizations of experimentally deformed Carrara marble have lately shown that a significant porosity may emerge with dynamic recrystallization accommodated by sub-grain rotation 14 . It seems therefore that, like diffusion creep via GBS, dislocation creep might be involved to produce micro-pores via crystal plasticity.…”
Section: Introductionmentioning
confidence: 99%